Are there temporal subtypes of premenstrual dysphoric disorder?: Using group-based trajectory modeling to identify individual differences in symptom change - Eisenlohr-Moul, Tory A.; Kaiser, Gudrun; Weise, Cornelia; Schmalenberger, Katja M.; Kiesner, Jeff; Ditzen, Beate; Kleinstäuber, Maria (Psychological Medicine, 2020)
Background Premenstrual dysphoric disorder (PMDD) is a new Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 diagnosis characterized by the cyclical emergence of emotional and physical symptoms in the luteal phase of the menstrual cycle, with symptom remission in the follicular phase. Converging evidence highlights the possibility of distinct subtypes of PMDD with unique pathophysiologies, but temporal subgroups have yet to be explored in a systematic way.Methods In the current work, we use group-based trajectory modeling to identify unique trajectory subgroups of core emotional and total PMDD symptoms across the perimenstrual frame (days-14 to +9, where day 0 is menstrual onset) in a sample of 74 individuals prospectively diagnosed with DSM-5 PMDD.Results For the total daily symptom score, the best-fitting model was comprised of three groups: a group demonstrating moderate symptoms only in the premenstrual week (65%), a group demonstrating severe symptoms across the full 2 weeks of the luteal phase (17.5%), and a group demonstrating severe symptoms in the premenstrual week that were slow to resolve in the follicular phase (17.5%).Conclusions These trajectory groups are discussed in the context of the latest work on the pathophysiology of PMDD. Experimental work is needed to test for the presence of possible pathophysiologic differences in trajectory groups, and whether unique treatment approaches are needed.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Group-based trajectory modeling; menstrual cycle; premenstrual dysphoric disorder; premenstrual syndrome